The grain boundary effect on electromechanical property of ferroelectric ceramics. (15th March 2020) - Zhao, X.F.; Soh, A.K.
Abstract: The extended Eshelby method and Ginzburg-Landau theory have been employed to investigate the effect of grain boundary on the microstructure behavior and electromechanical property of BaTiO3 ceramics with no prior constraint on the grains' shape and material parameters. The results obtained show that, the ferroelastic property of grain boundary plays an important role on the domain structure, ferroelectric and electromechanical properties of ferroelectric ceramics by affecting the elastic and electrostatic field of the material. The macro-properties of ferroelectric ceramics could be effectively functionalized by controlling the average grain size and ferroelastic field of the structure. Graphical abstract: Image, graphical abstract